x^2-1=1+y/2 1-y^2=2+x x^y=(2,x^4*y)

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:
53 уравнение:

Решение

Вы ввели
[LaTeX]
 2           y
x  - 1 = 1 + -
             2
$$x^{2} - 1 = \frac{y}{2} + 1$$
     2        
1 - y  = 2 + x
$$- y^{2} + 1 = x + 2$$
 y        4   
x  = (2, x *y)
$$x^{y} = \left ( 2, \quad x^{4} y\right )$$